Synthesis And Characterization Of Carbon-Chitosan Composite Electrodes Based On Biomass Carbon Activated Using The Microwave Method - Nurdandi, Deden; Aldila, Herman; Kurniawan, Widodo Budi (Jurnal Riset Fisika Indonesia, 2022)
English